Kebijakan Hukum Terhadap Pelaku Tindak Pidana Pencucian Uang - Henry Afrillo; Hudi Yusuf (CV. ITTC INDONESIA, 2024)
During the period of globalization and swift technological advancement, money laundering has become a serious threat to economic stability and the financial system in Indonesia. Money laundering not only harms the country through the loss of potential tax revenue but also compromises the steadiness and dependability of the financial system while creates opportunities for organized crime. This research aims to analyze current legal policies, identify challenges in law enforcement, and assess the the impact and efficiency of Law Number 8 of 2010 on Preventing and Combating Money Laundering. The methodology applied is a case study with a document analysis approach, examining the implementation of policies through various real cases and empirical data. Findings from the research demonstrate that despite a clear legal framework and the involvement of relevant institutions, significant challenges still hinder law enforcement, including the complexity of financial transactions, lack of coordination among government agencies, and limited human resources in handling money laundering cases. Furthermore, the lack of public awareness regarding the dangers of money laundering also exacerbates this situation. To enhance the effectiveness of policies in combating money laundering, there is a need for regulatory updates that keep pace with the evolving modus operandi of criminals. Additionally, training for enforcing the law and increased collaboration on an international level is essential to strengthen networks for prevention and law enforcement. The recommendations generated from this study are expected to strengthen the robustness and trustworthiness of the financial framework in Indonesia and protect society from the negative impacts of money laundering.